1994
DOI: 10.1136/jech.48.2.156
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology of peptic ulcer: a prospective population study in Norway.

Abstract: Study objective -To analyse simultaneously the effect of several risk factors for peptic ulcer. Design -Cohort study where all patients with new or incident peptic ulcers in a well defined population were registered for a seven year period. The follow up started with a comprehensive health survey including a questionnaire on diet, lifestyle, psychological and social conditions, and health. Relative risks, both sex specific and separate, for gastric and duodenal ulcers were estimated from proportional hazard re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
3

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 26 publications
3
26
3
Order By: Relevance
“…Fermented milk has been shown to reduce gastric emptying, a fact that could be of importance for an antagonistic effect between lactic acid bacteria and H. Pylori (Strandhagen et al, 1994) The bactericidal effect of milk and colostrum disappeared after heating (Stro Èmqvist et al, 1995). This is consistent with ®ndings in this and other studies showing no positive effect of milk consumption on the occurrence of peptic ulcer (Johnsen et al, 1994;Mullan et al, 1994).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Fermented milk has been shown to reduce gastric emptying, a fact that could be of importance for an antagonistic effect between lactic acid bacteria and H. Pylori (Strandhagen et al, 1994) The bactericidal effect of milk and colostrum disappeared after heating (Stro Èmqvist et al, 1995). This is consistent with ®ndings in this and other studies showing no positive effect of milk consumption on the occurrence of peptic ulcer (Johnsen et al, 1994;Mullan et al, 1994).…”
Section: Discussionsupporting
confidence: 82%
“…High intake of fermented milk was associated with fewer ulcers, whereas increased risk of peptic ulcer was observed among subjects with a high milk intake. The increased risk of peptic ulcer and milk intake is consistent with previous reports (Johnsen et al, 1994;Ippoliti et al, 1976). One explanation might be that milk and the high calcium content has a stimulative effect on acid secretion, although the intake of milk might reduce symptoms.…”
Section: Discussionsupporting
confidence: 80%
“…Findings in a previous Norwegian study did not support the concept that peptic ulcer is a psychosomatic disorder [15] . However, childhood adversities have been found in association with other diseases, for example coronary heart disease [16] and migraine [17] , and also with disability pensions [18] .…”
Section: Discussioncontrasting
confidence: 48%
“…In contrast, a recently conducted retrospective observational study, 10 showed an association between psychological stress and PUD independent of other known risk factors (H. pylori infection and NSAID use). Johansen et al, 11 argued that some reports of associations between exposure to psychosocial stress and PUD may be unreliable, as both exposure and CI, confidence interval; HR, hazard ratio; n, number; SEI, socioeconomic index.…”
Section: Discussionmentioning
confidence: 99%
“…Stressful life events have been associated with increased PUD risk in some studies, 2, 7-10 but others did not find this. 5,6,[11][12][13] Earlier studies on the relationship between psychosocial stress and PUD have not been able to clearly identify that stressful exposures pre-dated disease onset. 2 As there is notable variation in stress susceptibility between individuals, 14,15 this characteristic prior to symptomatic onset of peptic ulcer may be a useful tool to elucidate the role of psychosocial stress as risk factor for PUD.…”
Section: Introductionmentioning
confidence: 99%